THE APPLICATION OF COMIC STRIPS TO IMPROVE THE FIRST YEAR STUDENTS WRITING ABILITY OF SMAN 9 PEKANBARU - Yulizar Kiki Wardhany Kiki Wardhany; Rumiri Aruan Rumiri Aruan; Desri Maria Desri Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this research was to find out if the application of comic stripscould improve students’ writing ability of the first year students of SMA Negeri 9Pekanbaru.The participants were 35 students. The data was collected by usingobservation sheets, writing tests, and field notes. The test was used to collect thequantitative data and the observation sheets were used to collect the qualitative data.After accomplishing this research, the writer concludes that the application of comicstrips in writing recount text can improve the students’ writing ability. The result of pretestshows the average score of students writing ability was 37.94%. It improved to46.86% on the post-test in cycle 1, 54.73% on the post-test in cycle 2, and 62.83% onthe post-test in cycle 3. It was also proved that that the application of comic strips couldimprove the students’ behavior in learning especially in writing ability. They are moreactive and have a great motivation during the process of teaching and learning sincethey are free to explore their idea and share to their friends. In addition, applicationcomic strips could also improve students’ ability to write English in terms of grammar,vocabulary, pronunciation, fluency, and comprehension.Keywords: Application Comic Strips, Writing Ability, Recount Text